PENINGKATAN KEAMANAN IMIGRAN ASING OLEH PEMERINTAH INDONESIA DEMI CEGAH PENULARAN VIRUS COVID-19 - Martha Nindya Pratyaksa; Fatma Ulfatun Najicha (Fakultas Hukum Universitas Borneo Tarakan, 2022)
AbstractCurrently, the transmission of the COVID-19 pandemic virus in Indonesia is part of the 2019 coronavirus disease pandemic (COVID-19) that is ongoing worldwide. This disease is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which transmission can be through foreign immigrants. This affects the amendment of Government Regulation Number 31 of 2013 concerning Immigration to Government Regulation Number 48 of 2021 concerning Immigration in which there is the addition of new rules to Government Regulation Number 48 of 2021 concerning Immigration article 103 number 1 part (d)